THE INFLUENCE OF PRODUCT QUALITY ON CONSUMER SATISFACTION AT WADAH KOPI 27, CENTRAL JAKARTA - Darsiah, Anis; Artina Sembiring, Vienna; Octarina, Dian (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
Coffee shop is a place (tavern) that serves processed espresso coffee and small snacks as the era of coffee shop provides snacks and heavy meals. The development of coffee shops in Indonesia is very widespread, coffee drinks are also liked by the public in all circles. With the wide development in the coffee shop, the quality of products becomes an important thing and the quality of good products of the community / consumers will feel satisfied. Based on this, researchers conducted a study to find out how much the influence of product quality on consumer satisfaction in one of the coffee shops is Wadah Kopi 27 Central Jakarta. The method used in this study was descriptive and correlational with the quantitative approach of data obtained from the dissemination of questionnaires to a total of 94 respondents. Sample collection method using simple random sampling. Technique. Data analysis processing using SPSS version 25. The results of this study, it can be concluded that product quality found the simultaneous influence of product quality on consumer satisfaction